Program Kemitraan Masyarakat (PPMU-PKM) Kelompok Nelayan “Bakau” Penangkap Rajungan di Dusun Lantebung, Kelurahan Bira, Kecamatan Tamalanrea, Makassar - Mahfud Palo; Najamuddin Najamuddin; Andi Marimba; Mukti Zainuddin; M Hajar; muhammad Kurnia (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
The Community Service Activity (PPMU-PKM) aims to carry out one of the Tridarma duties of Higher Education. The main activity in community service is to provide knowledge and modeling for fishing communities, improve the ability of fishermen to manage crab resources sustainably. This activity was held from July to October 2018 in Lantebung Hamlet, Bira Village, Tamalanrea District, Makassar. There are 2 main activities carried out, namely counseling on fishermen from KUB members "Bakau" and ranching the egg-laying crabs caught by fishermen until the crabs release their eggs. It is expected that these eggs will increase the crab population in the waters around the service location.